Belonging, pausing, feeling: a framework of "mobile dwelling" for U.K. university students that live at home. Issue 1 (2nd January 2020) - Holton, Mark; Finn, Kirsty
Abstract: Notions of place and dwelling have become increasingly dynamic of late. No longer is place considered the sedentary equivalent to mobility, instead the spaces at which place and mobility intersect have produced exciting new ways of thinking about liminoid and mobile places, and how one might dwell in and through these intersections. In this paper we develop a framework of mobile dwelling to better understand student mobilities within UK higher education (HE), a sector that is framed by a set of binary dualisms – mobile/immobile, home/away, local/non-local. This dualistic thinking about im/mobility reflects the legacy of the "boarding school" model attached to traditional (and elite) HE participation, and newer permutations of undergraduate entry which is increasingly skewed towards the local. The framework developed here challenges these binary conceptualisations, which unhelpfully cast the growing number of live-at-home (LAH) students as immobile, writing out everyday movements such as commuting, and social and digital interactions with (and off) campus. Thus, by applying our concept of mobile dwelling to two UK-based studies, we reveal the complexities of LAH students' daily mobilities; illuminating the pauses, the senses of belonging and the emotional reflections that are afforded by performances associated with commuting. By approaching everyday mobility as a tripartite experience of dwelling within/upon the liminoid spaces and experiences that constitute HE, we provide tools for understanding how marginal students make sense of their own identities, relationally understood against more traditional notions of studenthood.